Properties and applications of rare-earth doped fiber amplifiers and lasers. - Barnard, Chris. (University of Ottawa (Canada), 1994)
An analytical model for two-, three-, and four-level system rare-earth-doped fiber amplifiers and lasers is presented. Fiber amplifier gain is expressed in terms of easily measured attenuation coefficients, intrinsic saturation powers, and cross saturation powers at the pump and signal wavelengths. System-independent formulas are given for the slopes and thresholds of ring and linear fiber lasers. Good agreement between theory and experiment is shown for erbium-doped fiber amplifiers and lasers and thulium-doped fiber lasers. Approximate system-independent solutions are also given for fiber amplifiers with excited state absorption at either the pump or signal wavelengths. A novel technique, requiring only one tunable light source, is proposed for finding the best pump wavelength when pump ESA is present. Analysis of erbium doped fiber amplifier (EDFA) gain and noise yields a new expression for the amplifier signal-to-noise ratio (SNR) as a function of the fiber length. This leads to a new expression for the fiber length that optimizes the output SNR. Optical gain switching of EDFAs with short pulses at wavelengths within the amplifier bandwidth is modelled to determine how the pump and signal powers, pulse energy, fiber length, and dopant concentration affect the switching time and gain compression. Greater than 20 dB gain compression with nanosecond switching times is demonstrated with good agreement between theory and experiment. Remote EDFA switching from as far as 50 km away is demonstrated. The distance is limited by spontaneous Raman scattering of the switching pulses. These limitations are experimentally and theoretically investigated. Novel configurations are proposed for bidirectional amplification in both single-mode fiber and polarization maintaining fiber. New frequency dependent optical isolators are demonstrated for OTDR testing of amplified fiber links. The new bidirectional amplifier design is much better at attenuating backreflections than a standard EDFA. Polarization separated bidirectional fiber local area networks are proposed. Point-to-point and reflective N-star coupler networks where N = $M\sp2$ or 2$M\sp2$ are considered for an integer M. Reflective star coupler networks use a novel proposed fiber device: an orthogonal polarization variable reflector which can act as an orthogonal polarization full or half reflector. A bidirectional fiber amplifier configuration for polarization separated signals is also proposed.
Keywords: Engineering, Electronics and Electrical.